A continental analysis of correlations between tree patterns in African savannas and human and environmental variables - Groen, T.A.; van Langevelde, F.; van de Vijver, C.A.D.M.; de Raad, A.L.; de Leeuw, J.; Prins, H.H.T. (Journal of arid environments, 2011)
This study analyses possible relationships between natural processes taking place in savannas and the tree patterns found in savannas. This can lead to new hypotheses about which processes are driving savanna physiognomy. To do so tree patterns were quantified for African savannas from historical aerial photographs applying frequently used landscape metrics. Also, additional data for these areas were collected to quantify the processes taking place at these locations. Correlations between tree pattern indices and explaining factors were analysed. We found a negative trend between tree cover and density of sheep and goats, but no relationship between tree cover and density of cattle, suggesting that small livestock have an effect on tree cover, but that larger livestock (or obligate grazers) do not. Also, a positive correlation between human population density and tree cover was found. Possible explanations for the found relations are discussed. Subsequent ways to analyse the latter correlation are discussed, and the potential of the presented historical database of aerial photographs is highlighted. ► Tree patterns in historical areal photographs were quantified. ► These patterns were correlated with processes. ► Sheep and goat density had a negative correlation with tree cover. ► Human population density had a positive correlation with tree cover.